Teachers' Perceptions of Students' Creativity in China's Classrooms: The Role of Students' Academic Achievement and Misbehaviors. (22nd April 2020) - Guo, Jiajun; Tong, Yao; Pang, Weiguo
Abstract: Teachers can be biased, especially toward low achievers and students with behavioral issues. However, creative students often appear to be disruptive in the classroom, and many of them struggle academically. The purpose of the present study was to examine the extent to which teachers' perceptions of students' creativity is associated with students' academic achievement and classroom (mis)behaviors, as well as to examine the interaction between these two factors. Three hundred and fifty‐four eighth‐grade students selected from five middle schools in China participated in this study. Using achievement scores, peer nominations, a divergent thinking test, a self‐rated ideational behavior scale, and teacher ratings, the present study found that, whereas creativity has no significant relationship with teachers' perceptions, academic achievements and misbehavior are significantly associated within structors' perceptions. The achievement bias resulted in the underestimation of low achievers' creativity, even when the low achievers were highly creative. More nuances emerged when student misbehaviors were considered. Specifically, misbehaving low achievers' originality was further underestimated even when they were highly original. In contrast, teachers overestimated well‐behaved high achievers' creativity, even when the students comprised the lowest creativity group. The results are further discussed from a socio‐cultural perspective.